Creative Expression and the Material Culture of Italian POWs in the United States During World War II - Ruberto, Laura E. (Material Culture Review / Revue de la culture matérielle)

(untitled) (Cape Breton University Press, 2022)
This study concerns the history of Italian prisoners of war in the United States during World War II through an analysis of the art and architecture they created. These crafted expressions highlight how Italian culture was transported and reshaped during the war and suggest alternate understandings of Italian diasporic culture and wartime experiences. They reinforced cultural heritage, mediated personal and community identities, and negotiated some of the atrocities of war. As a cultural studies scholar engaging with Italian transnational concerns, my approach emerges from an interest in the use of space, place-making, and the meanings ascribed to the material world.